Wittgenstein's Mistress - Markson, David; Wallace, David Foster (Champaign, IL : Dalkey Archive Press, 2015)
"Wittgensteins Mistress is the story of a woman who is convinced - and may ultimately convince the reader as well - that she is the only person left on earth. So appealing is her character, and so witty and seductive her narrative voice, we follow her hypnotically as she unloads the intellectual baggage of a lifetime in a series of irreverent meditations on everything from Brahms to sex to Heidegger to Helen of Troy. And as she contemplates aspects of the troubled past that have brought her to her present state, so too will her drama become one of the few certifiably original fictions of our time"--Page 4 of cover
Second printing, 2015
With an afterword by David Foster Wallace
Text in English
Keywords: Women -- Fiction; Long Island (N.Y.) -- Fiction; Psychological fiction; Philosophical fiction; Novels